Assessing new strategies for TB diagnosis in low- and middle-income countries - Afrânio Kritski (Brazilian Journal of Infectious Diseases)
In this manuscript, we report the current situation of tuberculosis globally and in Brazil, the need for new strategies toward tuberculosis control, focusing on new diagnostic technologies. Critical comments are given on the state of the art regarding the evaluation of new health technologies, degree of scientific evidence needed, evaluation of clinical impact, cost-effectiveness of incorporation into the health system and the social impact.